Analysis on CO2 reforming of CH4 by corona discharge process for various process variables - Hoang Hai Nguyen; Nasonova, Anna; Nah, In Wook; Kim, Kyo-Seon (ELSEVIER SCIENCE INC, 2015)
The CO2 reforming of CH4 to syngas by corona discharge at atmospheric pressure has been investigated for various process variables. The experiments were operated systematically in wide regions of process variables such as CO2/CH4 ratio, total flow rate, pulse frequency and applied peak voltage. The conversions of methane and carbon dioxide increase with increasing the applied peak voltage or pulse frequency and decrease with increasing the total flow rate. Selectivities of H-2 and CO increase with the increase of applied peak voltage, while increasing total flow rate and pulsed frequency does not affect H-2 and CO selectivities significantly. (C) 2015 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: CARBON-DIOXIDE; METHANE CONVERSION; NONTHERMAL PLASMA; PARTIAL OXIDATION; CATALYSTS; SYNGAS